EFISIENSI SDM DENGAN CUSTOMER RELATIONSHIP MANAGEMENT BERBASIS WEB DAN SMS GATEWAY - Sudarmanto; Hera Wasiati (LPPM STMIK El Rahma Yogyakarta, 2021)
This study aims to develop an application for improving HR efficiency by applying the concept of web-based and SMS Gateway Customer Relationship Management (CRM). The study is used as a tool to help in providing information to the general public and patients, especially those with Tuberculosis in the Community Centre for Lung Health (BKPM) of Klaten Regency. The CRM system in BKPM Klaten is used to efficiently manage patients and all health information. This application will provide information including medical check-up timing and manage appointments with patients more effectively to improve medical staffs’ schedule efficiency. The patients’ notification method is using SMS Gateway (Short Message Service). This research implemented a survey and an interview to the agency and analyze the system that was running in BKPM Klaten as its research method. The development of this system uses both Data Flow Diagrams (DAD) and Relationship Between Tables methods. The application is expected to improve the efficiency of human resources management in BKPM Klaten in doing its job of providing information to the public, arranging required reports, and specifically for the patients, impacting on increasing the customers’ satisfaction and loyalty. This system can also make it easier for BKPM to interact directly with patients using an SMS gateway.